Blue light excited wide half-width near-infrared fluorescent ceramics and preparation method and application thereof
By using blue-light-excited (Gd1-xCax)3(Sc1-yCry)2(Al1-zSiz)3O12 ceramics in near-infrared luminescent materials, the problems of low luminescence efficiency and half-height width and narrow emission spectrum are solved, and the problem of low luminescence efficiency of existing materials is achieved. High stability and broadband near-infrared luminescence, suitable for food testing and medical fields.
Patent Information
- Application Number
- CN202310357588.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2023-02-24
- Filing Date
- 2023-04-06
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-04-06
AI Technical Summary
Existing near-infrared luminescent materials have problems such as low luminescence efficiency, semi-height and narrow emission spectrum, and neglecting the valence state of Cr ions, which is difficult to meet the needs of broadband near-infrared fluorescent materials.
(Gd1-xCax)3(Sc1-yCry)2(Al1-zSiz)3O12 near-infrared fluorescent ceramics excited by blue light, the main peak of the emission spectrum is between 780-850nm and the half height is between 240-280nm under blue light excitation. During the period, the Cr3+ charge stability is maintained through the doping of Ca2+ and Si4+ to ensure that the valence state of the Cr ion in the luminescent center is +3.
Near-infrared fluorescent ceramics with high luminescence stability, wide, half, and low heat quenching are achieved, and are suitable for food testing and medical fields.
Smart Images

Figure CN116639975B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of near-infrared luminescent ceramic materials, and in particular to a blue light excited wide half-width near-infrared fluorescent ceramic and a preparation method and application thereof. Background Art
[0002] Near-infrared spectroscopy has the advantages of being non-destructive, fast in response and pollution-free, and has been widely studied in fields such as food testing and medical treatment. Short-wave near-infrared is usually divided into a range of 780nm to 1100nm, which covers the frequency harmonics and sum frequency characteristics of the vibration of hydrogen-containing groups (O-HN-H CH). When a light-emitting device in this band is used to illuminate the object to be tested, specific substances will absorb specific light bands, and the substance and content can be determined based on the information of the spectrum. Therefore, short-wave near-infrared spectroscopy has been increasingly applied, and in-depth research on near-infrared luminescent materials is of great significance.
[0003] Traditional tungsten filament lamps and halogen lamps are large in size, short in life, and low in efficiency, which limits the development of lightweight, miniaturized and portable devices. Although LED-type near-infrared has the advantages of small size, long life, and high luminous efficiency, its narrow bandwidth is not enough to meet the emission spectrum requirements of near-infrared light sources. Therefore, there is an urgent need to develop high-quality and high-performance near-infrared fluorescent materials. As a typical transition metal ion, trivalent Cr has outstanding advantages in near-infrared luminescent materials. Its emission range is from deep red to near infrared, and it has strong absorption peaks in the visible spectrum (ultraviolet, blue light), which is very compatible with commercial blue LED chips. In recent years, the use of Cr 3+ As a near-infrared luminescent center, near-infrared fluorescent materials have made great progress. Chinese patent CN111117618B discloses a chemical formula of Gd 3-x Re x Sc 2-y-z Cr y Al z Ga3O 12 broadband near-infrared fluorescent material. The core of this patent is Ga 3+ The ions occupy the entire tetrahedral lattice of the matrix, and its octahedral lattice also contains Sc 3+ and Al 3+ Therefore, the emission spectrum of the material is wide (700-1000nm). Chinese patent CN114058372A discloses a chemical formula A 2-y Ln y BAl 4-x Cr x SiO 12 Near-infrared phosphor, this patent mainly uses Cr 3+ -Ln 3+The energy transfer between the two broadens the emission range of the phosphor (600nm-1100nm). X 3Sc2Ga3O 12 ( X = Lu, Y, Gd, La) series of near-infrared phosphors, by adjusting the dodecahedral cation, the half-height width of the phosphor is expanded from 73nm to 145nm, but its thermal stability also decreases. 2+ -Si 4+ Co-replacement Y 3+ -Al 3+ Prepared Y 3- x Ca x Al 5-x Si x O 12 :Cr near-infrared phosphor, the maximum half-width of the emission spectrum of this phosphor is 160nm. However, the paper did not change the composition of the matrix octahedral lattice.
[0004] Chinese patent CN 113213933 A discloses a chemical formula Y 3-x-z A x Al 5-x-y Si x O 12 : y Cr 3+ , z Yb 3+ Near-infrared fluorescent ceramics. From the perspective of composition, the near-infrared ceramics published in this patent all contain Y element and account for a large proportion. From the perspective of the crystal field environment of the luminescent center, the main peak of the luminescent ion emission in this patent is mainly affected by Y 3+ and the influence of the A ion. Chinese patent CN 113817468 A discloses a chemical formula (A x B y )2C4D5O 18 :aCr 3+ ,bRE's Cr 3+ Cordierite doped near-infrared phosphor, from the composition analysis, the patent published near-infrared phosphor has 18 oxygen components, which can be Cr 3+ Provide a variety of crystallographic lattices, thereby obtaining wide half-width emission characteristics. Chinese patent CN 113817468 A discloses a chemical formula A x B y Cz O q D p Near-infrared luminescent materials, where 5≤q≤7, can obtain a wider half-width according to the method of the patent. However, as shown in the patent, their internal quantum efficiency is low (IQE is 14.1%, 18.4%, etc.).
[0005] In summary, the current near-infrared luminescent materials have problems such as low luminescence efficiency, narrow half-height width of emission spectrum, and neglect of Cr ion valence state. 3+ Valence-stable near-infrared fluorescent ceramics are of great significance. Summary of the invention
[0006] In order to solve the problems of thermal quenching and narrow emission spectrum of near-infrared luminescent materials, the present invention proposes a blue light-excited wide half-width near-infrared fluorescent ceramic and a preparation method and application thereof. The main peak of the emission spectrum of the fluorescent ceramic under blue light excitation is between 780-850nm, the half-width is between 240-280nm, and the valence state of the Cr ion in the luminescent center is +3.
[0007] In order to solve the above technical problems, the present invention provides a near-infrared fluorescent ceramic for use in the fields of food detection and medical treatment, which has the characteristics of stable luminescence, high half-width, and small thermal quenching. The technical solution adopted by the present invention is: a blue light-excited wide half-width near-infrared fluorescent ceramic, whose chemical formula is: (Gd 1-x Ca x )3(Sc 1-y Cr y )2(Al 1-z Si z )3O 12 ,in x Ca 2+ Doped dodecahedral Gd 3+ The mole percentage of lattice sites, y Cr is the luminescent center 3+ Octahedral Sc doped 3+ The mole percentage of lattice sites, z For Si 4+ Tetrahedral Al doped 3+ Mole percentage of lattice sites, 0.02≤ x ≤0.06,0.004≤ y ≤0.012,0.04≤ z ≤0.12, x : z =1:(1.5-2), the ceramic phase structure is gadolinium scandium aluminum garnet structure, Cr 3+ As the luminescence activation ion, Ca 2+ and Si 4+ The role is to maintain Cr3+ Charge-stabilized, hybridized luminescent ions surrounding dodecahedral Gd 3+ and tetrahedral Al 3+ Coordination environment, Sc 3+ It is an octahedral framework ion.
[0008] The present invention also provides a method for preparing the infrared fluorescent ceramic, and the preparation process is controllable.
[0009] In order to solve the above technical problems, the present invention proposes a method for preparing near-infrared fluorescent ceramics by solid phase reaction combined with high temperature sintering, and the specific steps include:
[0010] (1) According to the chemical formula (Gd 1-x Ca x )3(Sc 1-y Cr y )2(Al 1-z Si z )3O 12 The stoichiometric ratio of each element in the mixture is as follows: gadolinium oxide, calcium carbonate, scandium oxide, chromium oxide, aluminum oxide and silicon dioxide with a purity greater than 99.9% are weighed as raw material powders, wherein x Ca 2+ Doped dodecahedral Gd 3+ The mole percentage of lattice sites, y Cr is the luminescent center 3+ Octahedral Sc doped 3+ The mole percentage of lattice sites, z For Si 4+ Tetrahedral Al doped 3+ Mole percentage of lattice sites, 0.02≤ x ≤0.06,0.004≤ y ≤0.012,0.04≤ z ≤0.12, x : z =1: (1.5-2); add the raw material powder, ball milling medium and grinding balls into a ball milling jar for medium-speed ball milling to uniformly mix the mixed powder, add the grinding balls into the ball milling jar for medium-speed ball milling, the ball milling speed is 90r / min-100r / min, the ball milling time is 20h-30h, and the mixed powder is fully and uniformly mixed;
[0011] (2) Dry the ball-milled mixture in an oven at 45°C-50°C, and sieve the dried powder through a 50-80 mesh sieve 1-2 times;
[0012] (3) placing the sieved powder into a mold and molding it under pressure to obtain a near-infrared fluorescent ceramic blank;
[0013] (4) placing the near-infrared fluorescent ceramic blank in an inert atmosphere for high-temperature sintering at a temperature of 1460°C-1480°C for 2h-4h to obtain an unannealed near-infrared fluorescent ceramic;
[0014] Preferably, the ball milling medium is alcohol, and the ratio of alcohol to raw material powder is 2.5:3.5, with the units being mL and g respectively.
[0015] Preferably, the ball milling speed in step (1) is 95 r / min-100 r / min, and the ball milling time is 25 h-30 h.
[0016] Preferably, the calcium carbonate and silicon dioxide in step (1) are nanopowders with a particle size of 10-20 nm.
[0017] Preferably, the dried mixed powder in step (2) is sieved through a 50-60 mesh sieve 1-2 times.
[0018] Preferably, the high temperature sintering temperature in step (4) is 1470°C-1480°C, the temperature is kept for 3h-4h, and the heating rate during high temperature sintering is 0.1°C / min-0.5°C / min.
[0019] The present invention also provides application of the wide half-width near-infrared fluorescent ceramic excited by blue light.
[0020] The wide half-width near-infrared fluorescent ceramic can achieve near-infrared luminescence of 700-950nm under the excitation of a high-power blue light LED (2W-30W) or LD (1W-3W).
[0021] After the near-infrared fluorescent ceramics are remotely packaged with a blue light LED or LD, a near-infrared light-emitting device is obtained. The near-infrared light-emitting device can be used in the fields of food detection and biomedicine.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] (1) Ca provided by the present invention 2+ and Si 4+ The proportion and dosage can maintain the Cr in the crystal structure 3+ The charge is stable, so that the valence state of the Cr ion at the luminescence center of the near-infrared fluorescent ceramic is +3 at the dosage.
[0024] (2) The near-infrared fluorescent ceramic provided by the present invention has a main peak of emission spectrum between 780-850nm and a half-width between 240-280nm under blue light excitation. 2+ 、Si 4+The ratio and dosage can match the radii of the dodecahedron, octahedron and tetrahedron lattice ions in the ceramic matrix of the gadolinium-scandium-aluminum-garnet structure, and the dodecahedron Gd2+ around the hybrid luminescent ions can be formed without generating impurities. 3+ and tetrahedral Al 3+ Coordination environment, expanding the half-width of the ceramic emission peak.
[0025] (3) The near-infrared fluorescent ceramic provided by the present invention effectively solves the problem of narrow half-height width of near-infrared luminescent materials, and is simple to prepare and has controllable process. Under the excitation of high-power blue light LED (2W-30W) or LD (1W~3W), it can achieve near-infrared luminescence of 700-950nm.
[0026] (4) The near-infrared fluorescent ceramic provided by the present invention and the near-infrared light-emitting device packaged with LED or LD can be applied to the fields of food detection and biomedicine. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a physical picture of the near-infrared fluorescent ceramics prepared in Examples 1 to 3 of the present invention.
[0028] Figure 2 The XRD diagrams of the near-infrared fluorescent ceramics prepared in Examples 1 to 3 of the present invention are shown.
[0029] Figure 3 This is an emission spectrum diagram of the near-infrared fluorescent ceramic prepared in Example 3 of the present invention.
[0030] Figure 4 This is a SEM image of the near-infrared fluorescent ceramic prepared in Example 3 of the present invention.
[0031] Figure 5 This is the absorption spectrum of the near-infrared fluorescent ceramic in Comparative Example 1.
[0032] Figure 6 This is the absorption spectrum of the near-infrared fluorescent ceramic in Comparative Example 2.
[0033] Figure 7 This is the absorption spectrum of the near-infrared fluorescent ceramic in Comparative Example 3.
[0034] Figure 8 This is the emission spectrum of the near-infrared fluorescent ceramic in Comparative Example 4. DETAILED DESCRIPTION
[0035] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. The raw material powders used in the following embodiments are all commercially available products with a purity greater than 99.9%.
[0036] Example 1: Preparation (Gd 0.98 Ca 0.02 )3(Sc0.996 Cr 0.004 )2(Al 0.96 Si 0.04 )3O 12 :
[0037] (1) Press (Gd 0.98 Ca 0.02 )3(Sc 0.996 Cr 0.004 )2(Al 0.96 Si 0.04 )3O 12 According to the molar mass ratio of each element, high-purity Gd2O3, Sc2O3, Cr2O3, SiO2, and Al2O3 are accurately weighed, and the ball milling medium and raw material powder are mixed at a ratio of 2.5:3.5 (mL:g). Grinding balls are added to the ball mill for medium-speed ball milling at a speed of 90 r / min and a ball milling time of 30 h to ensure that the mixed powders are evenly mixed.
[0038] (2) The ball-milled mixture was dried in an oven at 45°C and the dried powder was sieved twice with a 50-mesh sieve.
[0039] (3) The sieved powder is placed in a mold and formed under pressure to obtain a near-infrared fluorescent ceramic blank, the density of which is 40% of the theoretical density of gadolinium scandium aluminum garnet.
[0040] (4) The green body was placed in an inert atmosphere and sintered at a high temperature of 1460°C at a heating rate of 0.5°C / min for 4 hours to obtain a near-infrared fluorescent ceramic.
[0041] Figure 1 The XRD pattern of the ceramic of this embodiment is as follows: Figure 2 As shown, it is shown that the ceramic is a gadolinium scandium aluminum garnet crystal phase. The main peak of the emission spectrum of the ceramic is at 780nm, the half-maximum width is between 240nm, and the valence state of the Cr ion in the luminescence center is +3.
[0042] Example 2: Preparation (Gd 0.96 Ca 0.04 )3(Sc 0.992 Cr 0.008 )2(Al 0.94 Si 0.06 )3O 12
[0043] (1) Press (Gd 0.96 Ca 0.04 )3(Sc 0.992 Cr 0.008 )2(Al 0.94 Si 0.06 )3O 12According to the molar mass ratio of each element, high-purity Gd2O3, Sc2O3, Cr2O3, SiO2, and Al2O3 were accurately weighed, and the ball milling medium and raw material powder were mixed at a ratio of 2.5:3.5 (mL:g). Grinding balls were added to the ball mill for medium-speed ball milling at a speed of 95 r / min and a ball milling time of 25 h to ensure that the mixed powders were evenly mixed.
[0044] (2) The ball-milled mixture was dried in an oven at 48°C and the dried powder was sieved twice with a 70-mesh sieve.
[0045] (3) The sieved powder is placed in a mold and formed under pressure to obtain a near-infrared fluorescent ceramic blank, the density of which is 42% of the theoretical density of gadolinium scandium aluminum garnet.
[0046] (4) The green body was placed in an inert atmosphere and sintered at a high temperature of 1470°C at a heating rate of 0.4°C / min for 3 hours to obtain a near-infrared fluorescent ceramic.
[0047] like Figure 2 The figure shows the XRD spectrum of the ceramic of this embodiment, indicating that the ceramic is a gadolinium scandium aluminum garnet phase. The main peak of the emission spectrum of the ceramic is at 820 nm, the half-maximum width is 265 nm, and the valence state of the Cr ion at the luminescence center is +3. Figure 1 It is the ceramic object of this embodiment.
[0048] Example 3: Preparation of (Gd 0.94 Ca 0.06 )3(Sc 0.988 Cr 0.012 )2(Al 0.88 Si 0.12 )3O 12
[0049] (1) Press (Gd 0.94 Ca 0.06 )3(Sc 0.988 Cr 0.012 )2(Al 0.88 Si 0.12 )3O 12 According to the molar mass ratio of each element, high-purity Gd2O3, Sc2O3, Cr2O3, SiO2, and Al2O3 were accurately weighed, and the ball milling medium and raw material powder were mixed at a ratio of 2.5:3.5 (mL:g). Grinding balls were added to the ball mill for medium-speed ball milling at a speed of 100 r / min and a ball milling time of 20 h to ensure that the mixed powders were evenly mixed.
[0050] (2) Dry the mixed powder in an oven at 50°C, and sieve the dried powder once through an 80-mesh screen. (3) Place the sieved powder into a mold and form it under pressure to obtain a near-infrared fluorescent ceramic blank, the density of which is 45% of the theoretical density of gadolinium scandium aluminum garnet.
[0051] (4) The green body is placed in an inert atmosphere and sintered at a high temperature of 1480°C at a heating rate of 0.5°C / min for 2 hours to obtain a near-infrared fluorescent ceramic.
[0052] The XRD spectrum of the ceramic in this embodiment is as follows Figure 2 As shown, it is shown that the ceramic is gadolinium scandium aluminum garnet phase. Figure 3 is the emission spectrum of the near-infrared fluorescent ceramic. Figure 4 This is a microscopic SEM image of the near-infrared fluorescent ceramic. The main peak of the ceramic emission spectrum is 850nm, the half-width is 280nm, and the valence state of the Cr ion at the luminescence center is +3. Figure 1 It is the ceramic object of this embodiment.
[0053] Comparative Example 1: Preparation (Gd 0.96 Ca 0.04 )3(Sc 0.996 Cr 0.004 )2(Al 0.96 Si 0.04 )3O 12
[0054] According to the process of Example 1 and the chemical formula of Comparative Example 1, near-infrared fluorescent ceramics were prepared. It was found that the valence state of Cr ions in the prepared ceramics was +4. This indicates that the charge in the matrix system is unbalanced. The absorption spectrum of the near-infrared fluorescent ceramics in Comparative Example 1 is as follows: Figure 5 shown.
[0055] Comparative Example 2: Preparation (Gd 0.94 Ca 0.06 )3(Sc 0.996 Cr 0.004 )2(Al 0.96 Si 0.04 )3O 12
[0056] According to the process of Example 1 and the chemical formula of Comparative Example 2, near-infrared fluorescent ceramics were prepared. It was found that the valence state of Cr ions in the prepared ceramics appeared +4. This indicates that the charge in the matrix system is unbalanced. The absorption spectrum of the near-infrared fluorescent ceramics in Comparative Example 2 is as follows: Figure 6 Shown
[0057] Comparative Example 3: Preparation (Gd 0.98 Ca 0.02 )3(Sc 0.996 Cr 0.004 )2(Al0.94 Si 0.06 )3O 12
[0058] According to the process of Example 1 and the chemical formula of Comparative Example 3, near-infrared fluorescent ceramics were prepared. It was found that the valence state of Cr ions in the prepared ceramics appeared +4. This indicates that the charge in the matrix system is unbalanced. The absorption spectrum of the near-infrared fluorescent ceramics in Comparative Example 3 is as follows: Figure 7 shown.
[0059] Comparative Example 4: Preparation (Gd 0.7 Ca 0.3 )3(Sc 0.996 Cr 0.004 )2(Al 0.7 Si 0.3 )3O 12
[0060] According to the process of Example 1 and the chemical formula of Comparative Example 4, near-infrared fluorescent ceramics were prepared. It was found that GdAlO3 appeared in the prepared ceramics, and the half-width height of the emission peak was only 96 nm. This indicates that too much Ca was introduced, resulting in the Gd3Sc2Al3O 12 The system's dodecahedron, octahedron, and tetrahedron lattice ion radius matching is unstable and cannot promote the widening of the half-height width. The emission spectrum of the near-infrared fluorescent ceramic in Comparative Example 4 is as follows Figure 8 shown.
[0061] Comprehensive examples and comparative examples 1-4 show that only suitable Ca 2+ 、Si 4+ ratio and dosage range to maintain Cr 3 + Stable and wide half-width emission of ionic valence states.
[0062] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A blue light excited wide half-width near-infrared fluorescent ceramic, characterized in that: Its chemical formula is: (Gd 1-x Ca x )3(Sc 1-y Cr y )2(Al 1-z Si z )3O 12 ,in x Ca 2+ Doped dodecahedral Gd 3+ The mole percentage of lattice sites, y Cr is the luminescent center 3+ Doped Octahedral Sc 3+ The mole percentage of lattice sites, z For Si 4+ Tetrahedral Al doped 3+ Mole percentage of lattice sites, 0.02≤ x ≤0.06,0.004≤ y ≤0.012,0.04≤ z ≤0.12, x : z =1: (1.5-2), the ceramic phase structure is a gadolinium scandium aluminum garnet structure; The method for preparing the wide half-width near-infrared fluorescent ceramic adopts mold forming combined with a solid phase reaction method to sinter at a high temperature to prepare a ceramic block, and specifically comprises the following steps: (1) According to the chemical formula (Gd 1-x Ca x )3(Sc 1-y Cr y )2(Al 1-z Si z )3O 12 The stoichiometric ratio of each element in the mixture is as follows: gadolinium oxide, calcium carbonate, scandium oxide, chromium oxide, aluminum oxide and silicon dioxide with a purity greater than 99.9% are weighed respectively as raw material powders; the raw material powders, ball milling media and grinding balls are added into a ball milling jar for medium-speed ball milling to uniformly mix the mixed powders; (2) drying the ball-milled mixture in an oven and then sieving it; (3) placing the sieved powder into a mold and molding it under pressure to obtain a near-infrared fluorescent ceramic blank; (4) sintering the green body at high temperature in an inert atmosphere to obtain the near-infrared fluorescent ceramic; The sintering temperature of the high temperature sintering in step (4) is 1460°C-1480°C, and the temperature is kept for 2h-4h. The heating rate during the high temperature sintering is 0.1°C / min-0.5°C / min.
2. The blue light excited wide emission band near-infrared fluorescent ceramic according to claim 1, characterized in that: The blue light excitation source is LED or LD, and the light emission range is 430nm-465nm.
3. A method for preparing the wide half-width near-infrared fluorescent ceramic according to claim 1, characterized in that: The ceramic block is prepared by sintering at high temperature using a mold forming method combined with a solid phase reaction method, which specifically includes the following steps: (1) According to the chemical formula (Gd 1-x Ca x )3(Sc 1-y Cr y )2(Al 1-z Si z )3O 12 The stoichiometric ratio of each element in the mixture is as follows: gadolinium oxide, calcium carbonate, scandium oxide, chromium oxide, aluminum oxide and silicon dioxide with a purity greater than 99.9% are weighed respectively as raw material powders; the raw material powders, ball milling media and grinding balls are added into a ball milling jar for medium-speed ball milling to uniformly mix the mixed powders; (2) drying the ball-milled mixture in an oven and then sieving it; (3) placing the sieved powder into a mold and molding it under pressure to obtain a near-infrared fluorescent ceramic blank; (4) The green body is placed in an inert atmosphere and sintered at a high temperature to obtain the near-infrared fluorescent ceramic.
4. The method for preparing the blue light excited wide emission band near-infrared fluorescent ceramic according to claim 3, characterized in that: In the step (1), the calcium carbonate and silicon dioxide are nanopowders with a particle size of 10-50 nm.
5. The method for preparing the blue light excited wide emission band near-infrared fluorescent ceramic according to claim 3, characterized in that: The ball milling medium in step (1) is alcohol, and the ratio of the ball milling medium to the raw material powder is 2.5 mL:3.5 g.
6. The method for preparing the blue light excited wide emission band near-infrared fluorescent ceramic according to claim 3, characterized in that: In the step (1), the ball milling speed is 90 r / min-100 r / min, and the ball milling time is 20 h-30 h.
7. The method for preparing the blue light excited wide emission band near-infrared fluorescent ceramic according to claim 3, characterized in that: In the step (2), the drying temperature is 45°C-50°C, and the dried powder is sieved 1-2 times with 50-80 mesh.
8. The method for preparing the blue light excited wide emission band near-infrared fluorescent ceramic according to claim 3, characterized in that: The density of the green body in step (3) is 40%-45% of the theoretical density of the near-infrared fluorescent ceramic.
9. The method for preparing the blue light excited wide emission band near-infrared fluorescent ceramic according to claim 3, characterized in that: The sintering temperature of the high temperature sintering in step (4) is 1460°C-1480°C, and the temperature is kept for 2h-4h. The heating rate during the high temperature sintering is 0.1°C / min-0.5°C / min.
10. Application of the blue light excited wide emission band near-infrared fluorescent ceramic obtained by the preparation method according to any one of claims 3 to 9 in fluorescence conversion type near-infrared LED / LD devices.
Citation Information
Patent Citations
A broadband near-infrared luminescent material, its preparation method and application
CN111117618B
Broadband near-infrared fluorescent ceramic, and preparation method and application thereof
CN113213933A
Oxide near-infrared light-emitting material, preparation method thereof and light-emitting device
CN113817468A
Near-infrared fluorescent powder, preparation method and application thereof
CN114058372A
Fluorescent ceramic with high thermal stability and high quantum efficiency for white LED / LD and preparation method thereof
CN112159220A
Cited By
High-strength and high-toughness composite structure microcrystalline ceramic as well as preparation method and application thereof
CN122426938A